PENGARUH KOMPRES HANGAT DENGAN BULI – BULI TERHADAP TINGKAT NYERI PUNGGUNG IBU HAMIL TRIMESTER III - Nurulicha, Nurulicha; Perwitasari, Perwitasari; Puspita Sari, Ayu Lestari (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
Low back pain (LBP) is one of several complaints frequently experienced by pregnant women throughout the world. The hormones relaxin and progesterone will relax the ligaments in the pelvic area and weight gain will change the size of the uterus to become larger, resulting in discomfort in the back area. To prevent the risks of pharmacological therapy, it is important to know complementary therapies that are effective and efficient. The aim of this study was to determine the effect of warm compresses using bladder media on the level of back pain in third trimester pregnant women. This research employed a quasi-experimental method with one group pre-post-test. The total sample of 28 respondents was taken from PMB